Tropical root crops - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1970)
A general description is given of cassava. Data deal with geographical distribution, production, yields and nutritional value, varietal improvement, agronomic practices, diseases and pests. Research activities in cassava are also described. (CIAT)